2015
DOI: 10.3389/fgene.2015.00334
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screening of mRNA Expression in Leprosy Patients

Abstract: Leprosy, an infectious disease caused by Mycobacterium leprae , affects millions of people worldwide. However, little is known regarding its molecular pathophysiological mechanisms. In this study, a comprehensive assessment of human mRNA was performed on leprosy skin lesions by using DNA chip microarrays, which included the entire spectrum of the disease along with its reactional states. Sixty-six samples from leprotic lesions (10TT, 10BT, 10BB, 10BL, 4LL, 14R1, and 10R2) and nine skin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 23 publications
(33 reference statements)
2
64
0
1
Order By: Relevance
“…We observed that two risk SNPs of PARL and all their captured SNPs were cis eQTLs for PARL mRNA expression in human blood ( P value from 5.6 × 10 −5 to 5.6 × 10 −24 ), and two risk SNPs of PINK1 were cis and trans eQTLs for PINK1 mRNA expression in skin ( P  = 1.5 × 10 −9 ) and blood ( P  = 3.1 × 10 −30 ), respectively. Nevertheless, we only found a significantly different expression of PINK1 mRNA, but not PARL mRNA, between leprotic lesions (leprosy per se or its subtypes) and control tissues based on the re-analysis of reported datasets1040. The exact reason for the discrepancy of PARL mRNA expression remains unknown and awaits future study.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We observed that two risk SNPs of PARL and all their captured SNPs were cis eQTLs for PARL mRNA expression in human blood ( P value from 5.6 × 10 −5 to 5.6 × 10 −24 ), and two risk SNPs of PINK1 were cis and trans eQTLs for PINK1 mRNA expression in skin ( P  = 1.5 × 10 −9 ) and blood ( P  = 3.1 × 10 −30 ), respectively. Nevertheless, we only found a significantly different expression of PINK1 mRNA, but not PARL mRNA, between leprotic lesions (leprosy per se or its subtypes) and control tissues based on the re-analysis of reported datasets1040. The exact reason for the discrepancy of PARL mRNA expression remains unknown and awaits future study.…”
Section: Discussionmentioning
confidence: 60%
“…We noticed that PARL mRNA expression level was extremely high in immune cells, but PINK1 had an extremely high mRNA expression in central nervous system. We observed a significantly differential mRNA expression of PINK1 , but not PARL , in leprosy skin lesions of 66 patients from the Gene Expression Omnibus dataset (GEO; http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE74481)40 (Table S4). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All datasets analyzed during the current study are available under NCBI's Gene Expression Omnibus repository accessions: GSE40950 [28], GSE35423 [14], GSE24280 [unknown], GSE443 [80], GSE17763 [81], GSE16844 [47], GSE74481 [82], GSE95748 [52], and GSE100853 [83].…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%